The Utility of Platelet Indices in Predicting Multiorgan Dysfunction in Scrub Typhus - Vijayakumar, Saravanakumari; Viswanathan, Stalin; Jain, Dheeraj (Interdisciplinary Perspectives on Infectious Diseases, 2020)
Platelet indices have been used to diagnose and prognosticate infections such as tuberculosis, malaria, dengue, and septic shock. Platelet indices have previously not been used in the prediction of multiorgan dysfunction (MODS) in patients with scrub typhus. A three-year retrospective review of patient charts was performed. Patients with and without MODS were compared. Platelet indices and other clinical and laboratory variables were used in logistic regression analysis to determine significant predictors. A ROC curve was generated with the platelet indices to predict MODS. Of 189 patients, 106 were male. Respiratory rate, serum creatinine, liver function tests, platelet count, thrombocytopenia <150 × 109/L, mean platelet volume (MPV) > 7.3 fL, and plateletcrit ≤0.19% varied significantly between patients with MODS and those without. Platelet indices are inexpensive and easily available. Only thrombocytopenia along with creatinine, alanine transaminase, and abnormal chest radiograph could significantly predict MODS in patients with scrub typhus.